2013
DOI: 10.1039/c2ce26120k
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide coordination compounds with 1H-benzimidazole-2-carboxylic acid: syntheses, structures and spectroscopic properties

Abstract: A flexible multidentate ligand, 1H-benzimidazole-2-carboxylic acid, was synthesized to construct a series of lanthanide coordination polymers [Ln(HBIC) 3 ] n (Ln = Eu (1), Tb (2), Gd (3), Pr (4), Nd (5); H 2 BIC = 1H-benzimidazole-2-carboxylic acid) under hydrothermal conditions. All the compounds were fully characterized by elemental analysis, IR spectroscopy, single-crystal X-ray diffraction, thermal analysis and various spectroscopic techniques. Structural analyses reveal that they are isostructural and fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 89 publications
1
27
0
Order By: Relevance
“…The Ln–O bond lengths are for two oxygen atoms of a chelate ligand coordinated to the same Ln centre. These intervals for the Ln–O bond lengths are also analogous to those observed in other lanthanide compounds with O‐donor ligands , …”
Section: Resultssupporting
confidence: 79%
“…The Ln–O bond lengths are for two oxygen atoms of a chelate ligand coordinated to the same Ln centre. These intervals for the Ln–O bond lengths are also analogous to those observed in other lanthanide compounds with O‐donor ligands , …”
Section: Resultssupporting
confidence: 79%
“…19.00 and 20.00 ppm attributable to the methyl groups attached to the p-cymene moiety, at ca. 22.00 ppm assigned to two methyl protons of the isopropyl groups, at around 31.00 and 31.50 ppm due to the CH resonance of the isopropyl group and in the range from 77.50 to 103.50 ppm due to aromatic carbons from p-cymene moiety. Furthermore, all complexes display signals in the range from 114.00 to 141.00 ppm related to the aromatic carbons from benzimidazole moiety, at 145.50 ppm from imidazole carbon, and at 164.00 ppm attributable to the carboxylate carbon.…”
Section: Spectroscopymentioning
confidence: 97%
“…The flexibility of the carboxylic group allows for various coordination modes in metal complexes, in which 1H-benzimidazole-2-carboxylate acts as a monodentate or bidentate chelating ligand. Recently, bidentate chelating, chelatingebridging, or bis(chelatingebridging) coordination modes have been reported for lanthanide complexes (Scheme 1) [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The added stability provided by their fused ring structures allows the N-substituents to be hydrogen atoms, as opposed to the bulky side groups utilized in most NHCs. [148][149][150][151] Gurau et al 152 found that bubbling CO2 into the ionic liquid 1-ethyl-3-methylimidazolium acetate, [EMIM]OAc, promoted the deprotonation of the cation by the acetate anion, generating acetic acid. Subsequent addition of CO2 to the generated carbene gave a complex which was crystallized as the [ 152 Finally, on a related note, N-heterocylic olefins (NHOs) have also been found to display remarkable reactivity towards CO2.…”
Section: B Imidazol-2-carboxylates and Related Complexesmentioning
confidence: 99%